1996
DOI: 10.1007/bf01271228
|View full text |Cite
|
Sign up to set email alerts
|

Monoamine oxidase gene transcription in human cell lines: Treatment with psychoactive drugs and ethanol

Abstract: In the present study transcriptional activities has been measured with different fragments of the 5'-flanking sequence of the human monoamine oxidase (MAO) genes linked to human growth hormone which was used as a reporter gene. SH-SY5Y neuroblastoma cells and 1242 MG glioma cells were compared under basal conditions as well as after treatments with different drugs. Under basal conditions, the relative reporter activities of the different promoter fragments were similar for both cell lines. No changes in promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 25 publications
(26 reference statements)
3
22
0
Order By: Relevance
“…30 The specific characteristics of the human MAOB gene promoter have been described and several fragments have been investigated with reporter gene assays. 29,31 For example, the maximal promoter activity for MAOB has been observed for a 0.15-kb GC-rich sequence close to the first exon of the gene. 29 Since no nuclear material is conferred to the platelets when they are released from the megakaryocytes, direct analysis of transcriptional regulation of MAO-B in platelets is not possible.…”
Section: Transcriptional Regulation Of Trbc Maomentioning
confidence: 99%
“…30 The specific characteristics of the human MAOB gene promoter have been described and several fragments have been investigated with reporter gene assays. 29,31 For example, the maximal promoter activity for MAOB has been observed for a 0.15-kb GC-rich sequence close to the first exon of the gene. 29 Since no nuclear material is conferred to the platelets when they are released from the megakaryocytes, direct analysis of transcriptional regulation of MAO-B in platelets is not possible.…”
Section: Transcriptional Regulation Of Trbc Maomentioning
confidence: 99%
“…Similar to GAPDH, the MAO B expression is increased by ethanol in brain cell lines. Previously, ethanol has been found to increase MAO B promoter activity and altered the transcription factors binding to the MAO B promoter in SH-SY5Y cells (Ekblom et al 1996), suggesting that ethanol may directly enhance the MAO B expression by induction of transcription factor(s). Recently, we found that ethanol significantly increased TIEG2 expression in SH-SY5Y cells (Lu et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This novel GAPDH–MAO‐B pathway may be therapeutically useful in combating the neuronal harmful effects of alcohol, previously demonstrated to increase MAO‐B activity and promoter transcription activity (Carlsson et al. 1980; Ekblom et al. 1996).…”
Section: Neuroprotective Effects Of 1‐(r)‐aminoindan: Insights From Imentioning
confidence: 96%
“…Also, 1-(R)-aminoindan decreased the ethanol-induced MAO-B activity and expression, prevented nuclear translocation of GAPDH and reduced cell death in human glioblastoma U-118 MG cells and neuroblastoma SH-SY5Y cells (Ou et al 2009). This novel GAPDH-MAO-B pathway may be therapeutically useful in combating the neuronal harmful effects of alcohol, previously demonstrated to increase MAO-B activity and promoter transcription activity (Carlsson et al 1980;Ekblom et al 1996). Combination exposure studies indicated that 1-(R)-aminoindan not only did not interfere with the neuroprotective activities of rasagiline or selegiline in PC-12 cells deprived of serum and nerve growth factor, but also possessed neuroprotective activity by itself, on the contrary to the neurotoxic effects of L-methamphetamine (Bar-Am et al 2004a).…”
mentioning
confidence: 98%